Graphene-integrated thermoplastic vulcanizates: Effects of in-situ vulcanization on structural, thermal, mechanical and electrical properties. Issue 2 (May 2023) - Sarfraz, Muhammad; Liaqat, Waqas A; Ali, Mohsin; Qaiser, Asif A
Gaining considerable attention as valuable plastic static-dissipative materials, conductive polymer blends are used as supercapacitors, light emitting diodes, artificial muscles and biosensors. Thermoplastic vulcanizates (PECVs) were prepared by blending ethylene propylene diene monomer (EPDM) and polypropylene (PP) thermoplastic via in-situ compatibilization technique by using a suitable compatibilizer and curing system. Electrically conducting graphene filler was incorporated into the blend to impart electroconducting properties. Maintaining a constant PP/EPDM ratio of 80:20 for all specimens, PECVs containing different loadings of graphene filler were prepared through in-situ compatibilization method. Fourier-transform infrared spectroscopy analysis was performed to investigate chemical changes ensued as a result of compatibilization reactions. Addition of graphene into the blended PECVs slightly improved their processability and thermally stable as confirmed by tests performed on Differential Scanning Calorimetery and Thermogravimetric Analyser. Mechanical aspects of the blends, inspected by operating Universal Testing Machine and Rockwell Hardness Tester, were substantially improved on account of blend compatibilization and addition of graphene. Their electrical properties measured through four-probe technique revealed significant improvement in electrical conductivity of compatibilized PECVs due to incorporation of graphene filler.